SOIL PROPERTIES AND NUTRIENT ELEMENT STATUS OF COCONUT LEAVES UNDER DEFFERENT CROPPING PATTERNS - Doah Dekok Tarigans (International Coconut Community, 1988)
This study was conducted to investigate the effects of six coconut cropping patterns on the soil properties and nutrient element status of coconut leaves. The experiments were carried out from August 1984 to May 1985 in Silang, Cavite, Philippines. Data on‑soil properties and nutrient element starus of coconut leaves were statistically analyzed in Randomized Block Design with three replications. Six cropping patterns in coconut with four species of perennial crops as intercrops, namely: banana, papaya, coffee and pineapple were used in this study. The organic matter, pH and cation exchange capacity of the soils did not differ significantly with cropping pattern although intensively cropped farms tended to have higher organic matter' and cation exchange capacity values. Nitrogen, phosphorus and potassium in the top soil were significantly higher in most intensive intercropped farms, but calcium and magnesium did not vary significantly. Moisture content, waterholding capacity, bulk density and particle density of the soil did not show significant difference with cropping patterns. Likewise, the number of bacteria, fungi and actinomycetes in the soil remained statistically the same. Leaf nitrogen and calcium, increased while potassium decreased with intensity of cropping. Phosphorus and magnesium showed no definite trend.